Thermo-mechanic and Microstructural Analysis of an Underwater Welding Joint - Hernández Gutiérrez, Pedro; Cepeda Rodríguez, Francisco; Ruiz Mondragón, José Jorge; Acevedo Dávila, Jorge Leobardo; Guerrero Mata, Martha Patricia; Guevara Chávez, Carlos Alberto (2016)
The aim of this research is to present a comparative analysis between theoretical and experimental thermal fields as well as a microstructural behaviour and residual stresses applying multiple weld beads in the joint of two API 5L X52 pipe sections. The thermal field, microstructural and residual stresses were numerically modelled through the finite element method (FEM) and compared to experimentally. The simulation conditions used in the FEM analysis were similar considerations to the underwater welding conditions. The finite element analysis was carried out, first by a non-linear transient thermal analysis for obtaining the global temperature history generated during the underwater welding process. Subsequently, a microstructural behaviour was determined using the temperatures distribution obtained in the pipe material by calculating the structural transformations of the material during the welding process, and finally a stress analysis was developed using the temperatures obtained from the thermal analysis. It was found that this simulation method can be used efficiently to determinate with accuracy the optimum welding parameters of this kind of weld applications.